Era Francia y no Italia. Conexiones, redes e influencias en la construcción del modelo turístico español (1880-1936) - Ana Moreno Garrido (Cahiers de Civilisation Espagnole Contemporaine)
While recognising the possible influence of other models, the construction of Spanish tourism was strongly conditioned by the French example. The French-Spanish tourism transfer was marked by three circumstances. First of all, there was the intense dialogue that both nations had maintained since the beginning of the 19th century, in which tourism was simply one more chapter. Secondly, the geographical proximity that enabled all learning processes to take place in a fluid and natural throughout the three shared tourist borders: the Atlantic, the Mediterranean and the colonial. And finally, the quantitative importance of their tourists. The study of this triple relationship and the extent to which this case can explore ways to analyse the many forms that transnationality takes in tourism is the subject of this article.